Standardized Laboratory Methodology for the Evaluation of Foraging Strategies in Necrophilous Beetles: A Case Study of Necrophila (Calosilpha) brunnicollis (Coleoptera: Silphidae) - Jakubec, Pavel; Kadlec, Jakub; Šípek, Petr (Journal of medical entomology, 2021)
Precise data regarding feeding habits of necrobiont species are a key element of food web and evolutionary ecology. They can also be used to assess the utility and value of those species for forensic entomology, where obligatory necrophagous species in particular are considered good bioindicators of postmortem or preappearance interval. However, the feeding habits of many species are known only from anecdotal field observations, often reduced to vaguely defined categories-predatory, necrophagous, or omnivorous. To address this issue, we designed a simple, in vitro behavioral experiment allowing the quantification of food preferences. Next, we applied it on Necrophila (Calosilpha) brunnicollis (Kraatz, 1877), which is a common carrion beetle of East Asia with unresolved food preferences. The results suggest that this species is preferentially necrophagous, thus valuable for forensic research. Importantly, however, our experimental design allowed us to reveal that it also readily feeds on larvae of Diptera, although they compose a minor proportion of its diet. This methodology can be applied to other species, and it could provide evidence for future decision making in forensic research.
Keywords: Forensic Entomology; Silphidae; Animals; Postmortem Changes; stravovací zvyklosti; brouci; mrtvola; zvířata; gender; Feeding Behavior; forenzní entomologie; Cadaver; Coleoptera; posmrtné změny; forensic entomology; food choice; necrophagy